2021
DOI: 10.3390/ncrna7030048
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role of Circular RNA–Protein Interactions

Abstract: Circular RNAs (circRNAs) are emerging as novel regulators of gene expression in various biological processes. CircRNAs regulate gene expression by interacting with cellular regulators such as microRNAs and RNA binding proteins (RBPs) to regulate downstream gene expression. The accumulation of high-throughput RNA–protein interaction data revealed the interaction of RBPs with the coding and noncoding RNAs, including recently discovered circRNAs. RBPs are a large family of proteins known to play a critical role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 100 publications
0
49
0
Order By: Relevance
“…They are rather more stable in comparison with their linear counterparts due to their resistance to ribonuclease (RNase) activities 25 . Circular RNAs have been proposed to function by means of miRNA sponging 26 , 27 , regulating transcription 28 , 29 and interacting with RNA-binding proteins (RBPs) 14 , 18 , 30 , 31 . Genome wide analysis has also demonstrated that circRNAs are evolutionary conserved among species 32 , 33 .…”
Section: Regulation Of Hippo-yap Signaling Axis By Circrnasmentioning
confidence: 99%
“…They are rather more stable in comparison with their linear counterparts due to their resistance to ribonuclease (RNase) activities 25 . Circular RNAs have been proposed to function by means of miRNA sponging 26 , 27 , regulating transcription 28 , 29 and interacting with RNA-binding proteins (RBPs) 14 , 18 , 30 , 31 . Genome wide analysis has also demonstrated that circRNAs are evolutionary conserved among species 32 , 33 .…”
Section: Regulation Of Hippo-yap Signaling Axis By Circrnasmentioning
confidence: 99%
“…Due to the closed circular nature, circRNAs are resistant to exonucleases and very stable compared to linear RNAs. circRNAs have been reported to regulate gene expression by acting as sponges for RNA-binding proteins (RBPs) and miRNAs ( Panda, 2018 ; Das et al, 2021 ). Also, a few circRNAs are translated into polypeptides with the cap-independent translation mechanisms, and some circRNAs regulate transcription by associating with snRNA and RNA pol II ( Bose and Ain, 2018 ; Sinha et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…CircRNAs are lncRNAs that are generated through backsplicing of 1 or more exons that is facilitated by RNA binding proteins (RBPs). CircRNAs can localize to the nucleus and cytoplasm and can be secreted through exosomes [ 110 , 111 ]. They can regulate gene expression both at the transcriptional and post-transcriptional level.…”
Section: Glis Circular Rnasmentioning
confidence: 99%